Short-Term Nutritional Support for Infants With Unrestricted Ventricular Septal Defects to Promote Postoperative Recovery - Qi-Liang Zhang; Qi-Liang Zhang; Qi-Liang Zhang; Qi-Liang Zhang; Shi-Hao Lin; Shi-Hao Lin; Shi-Hao Lin; Shi-Hao Lin; Wen-Hao Lin; Wen-Hao Lin; Wen-Hao Lin; Wen-Hao Lin; et al. (Frontiers in Pediatrics, 2022)
ObjectiveThis study is aimed to explore the effect of short-term nutritional support for infants with unrestricted ventricular septal defects on improving preoperative nutritional status and promoting postoperative recovery.MethodsThe clinical data of 35 infants with unrestricted ventricular septal defects who were treated with 2 weeks of nutritional support in our hospital from December 2020 to March 2021 were analyzed retrospectively. The clinical data of 38 infants with unrestricted ventricular septal defects who were treated in our hospital from May 2020 to October 2020 were selected as controls.ResultsThe preoperative body weight, preoperative albumin, preoperative prealbumin, and preoperative hemoglobin in the intervention group were significantly higher than those in the control group (P < 0.05). The postoperative ventilator time, intensive care time, and discharge time in the intervention group were significantly shorter than those in the control group (P < 0.05).ConclusionPerforming 2 weeks of nutritional support for infants with unrestricted ventricular septal defects can improve their preoperative nutritional status and promote postoperative recovery.